Evaluation of the tetrodotoxin uptake ability of pufferfish Takifugu rubripes tissues according to age using an in vitro tissue slice incubation method. (30th January 2020) - Gao, Wei; Yamada, Misako; Ohki, Rieko; Nagashima, Yuji; Tatsuno, Ryohei; Ikeda, Koichi; Kawatsu, Kentaro; Takatani, Tomohiro; Arakawa, Osamu
Abstract: The tetrodotoxin (TTX) uptake ability of pufferfish Takifugu rubripes tissues and its growth-associated changes were investigated using an in vitro tissue slice incubation method. Tissue slices prepared from the liver, skin, and intestine of a non-toxic cultured adult T. rubripes (20 months old) and incubated with incubation buffer containing 25 μg/mL TTX for 1–48 h showed a time-dependent increase in the TTX content in all tissues. The TTX contents of the skin and intestine slices were comparable to or slightly higher than that of the liver slices, with a similar transition pattern, suggesting similar TTX uptake ability among the skin, intestine, and liver. The TTX uptake ability of the liver and intestine did not differ significantly between young (8 months old) and adult (20 months old) fish, but the skin slices of young fish took up approximately twice as much TTX as that of adult fish, suggesting that the TTX uptake ability of the skin is involved in the growth-dependent changes in the toxin distribution inside the body in T. rubripes . To estimate the TTX uptake pathway in each tissue, an immunohistochemical technique was used to observe temporal changes in the intra-tissue microdistribution of TTX during incubation. The findings suggested that TTX is transferred and accumulates from pancreatic exocrine cells to hepatic parenchymal cells in the liver, from connective tissues to basal cells in the skin, and from villi epithelial cells via the lamina propria to the muscle layer in the intestine. Highlights: Tetrodotoxin (TTX) uptake ability of Takifugu rubripes tissues was examined. TTX uptake ability was similar in the skin, intestine, and liver. TTX uptake in the skin was ~2-fold higher in young fish than in adult fish. The TTX uptake pathway in each tissue was evaluated using immunohistochemistry.